Confessions of a grammar queen : a novel - Knight, Eliza (Sourcebooks Landmark, 2025)
"1960s New York. Bernadette Swift, a young copy editor at Lenox & Park Publishing is determined to become the first female CEO in the publishing industry. But first she needs to take the next step up that ladder with a promotion that her boorish and sexist boss wants to thwart. Every day at Lenox & Park is a series of jibs and petty inequities. Thank heavens Bernadette has her dog, Frank-a sweet and silly Great Dane-to encourage her and listen to her complaints. Seeking a more human, and female base of support Bernadette joins a feminist women's book club at the New York Public Library. Soon she's inspiring her fellow members to challenge the male gatekeepers and decades of ingrained sexism in their workplaces and pursue their personal and professional dreams. And that is precisely what Bernadette does on a daily basis: keeps her eye on the prize-equality for women in the workplace, and a promotion-while fending off the ire of her boss and the sabotaging efforts of a jealous coworker. With the support of her beloved Frank, her book club buddies, and a certain charismatic editor at Lenox & Park who has completely fallen for her, maybe, just maybe, Bernadette will prove able to claim victory for herself and the young women coming after her"--